Avaliação eletrofisiológica do sistema auditivo em indivíduos com gagueira desenvolvimental persistente - Regaçone, Simone Fiuza; Stenico, Mariana Banzato; Gução, Ana Cláudia Bianco; Rocha, Ana Cláudia Moraes; Romero, Ana Carla Leite; Oliveira, Cristiane Moço Canhetti De; Frizzo, Ana Claudia Figueiredo (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
ABSTRACT:Purpose: to describe the findings of electrophysiological examinations of individuals who stutter and compare with typically developing individuals.Methods: 34 subjects participated in this study, both genders, aged between 7 and 31 years. The research group consisted of 13 children (G1a) and 4 adults (G1b) diagnosed with stuttering and the control group of 13 children (G2a) with good academic performance and 4 fluent adults (G2b). The auditory potentials assessment was performed on frequency and duration discrimination tests.Result: when compared groups of stuttering children and control group, it was observed that the stuttering children had the scan frequency, increased latencies of P2, N2 components at Cz in the right ear and N2 and P3 at Fz in the left ear, and the difference amplitude P2 and P3 in the right ear Cz. In the scan duration, decreased the amplitude of the N2 and P3 components in Cz Fz in the right ear. In the group of adult stutterers was observed in the frequency sweep, increased latency P3 component at Cz and Fz in the right ear and reduced P3 amplitude at Cz in the left ear, and scan duration, increased latency of N2 Cz and P3 in the right ear and N2 at Cz in the left ear, when compared to the control group.Conclusion: there are differences between the electrophysiological examinations of individuals who stutter compared with those with typical development. However, further studies in this area are still needed for the findings presented here can be confirmed.

RESUMO:Objetivo: descrever os achados dos exames eletrofisiológicos de indivíduos com gagueira e comparar com indivíduos com desenvolvimento típico.Métodos: participaram desta pesquisa 34 indivíduos, de ambos aos gêneros, com idade entre 7 e 31 anos. O grupo pesquisa foi constituído por 13 crianças (G1a) e 4 adultos (G1b) diagnosticadas com gagueira e o grupo controle por 13 crianças (G2a) com bom desempenho acadêmico e 4 adultos (G2b) com desenvolvimento típico. Foi realizada a avaliação dos potenciais auditivos, na varredura de frequência e de duração.Resultado: quando comparados os grupos de crianças gagas e controle, foi observado que as crianças gagas apresentaram na varredura de frequência, aumento da latência dos componentes P2, N2 em Cz na orelha direita e N2 e P3 em Fz na orelha esquerda, e diferença na amplitude de P2 e P3 em Cz na orelha direita. Na varredura de duração, houve redução da amplitude dos componentes N2 em Cz e P3 em Fz na orelha direita. Já no grupo de adultos gagos, observou-se na varredura de frequência, aumento da latência no componente P3 em Cz e Fz na orelha direita e amplitude reduzida no P3 em Cz na orelha esquerda, e na varredura de duração, aumento de latência de N2 e P3 em Cz na orelha direita e N2 em Cz na orelha esquerda, quando comparados ao grupo controle.Conclusão: há diferenças entre os exames eletrofisiológicos de indivíduos com gagueira comparados aqueles com desenvolvimento típico. No entanto, novos estudos neste âmbito ainda são necessários para que os achados aqui apresentados possam ser confirmados.
Electrophysiology assessment of auditory system in individuals with developmental persistent stuttering
Keywords: Auditory Evoked Potentials; Stuttering; Auditory Perception; Potenciais Evocados Auditivos; Gagueira; Percepção Auditiva